Impact Of Play-Based Instruction And Jigsaw On Learning Motivation And Physical Fitness In Smk Tanjungpinang - Encik Nurissan Aprian; Umar Umar; Damrah Damrah; Nurul Ihsan (STKIP Singkawang, 2025)
This study investigates the influence of learning methods and student motivation on participation in Physical, Sport, and Health Education (PJOK) at SMK N 1 Tanjungpinang. The impetus for this research stems from observations indicating a low level of physical fitness among the student body, potentially attributable to a variety of factors, including pedagogical approaches and motivational levels. This quasi-experimental study involved 36 participants, selected based on pre- defined criteria. Physical fitness was assessed using the TKJI instrument, while motivation data were collected via a questionnaire. Data analysis was performed using a two-way analysis of variance (ANOVA) with a 2x2 factorial design. The results of the study and data analysis showed that: 1) There is a difference in physical fitness of students who are given the playing and jigsaw methods with a Sig value of 0.016 <0.05. 2) There is an interaction between learning methods and motivation on physical fitness, the Sig value between learning strategies and coordination skills is 0.000 < 0.05. 3) There is a difference in the level of physical fitness between students who are given the playing method and the jigsaw method at high learning motivation with a Qcount value of 14.54 > Qtable 3.85. 4) There is a difference in the level of physical fitness between students who are given the playing method and the jigsaw method at low learning motivation with a Qcount value of -2.65 < Qtable 3.85